2020
DOI: 10.3389/fpsyg.2020.540996
|View full text |Cite
|
Sign up to set email alerts
|

Creating Ambassadors of Planet Earth: The Overview Effect in K12 Education

Abstract: The overview effect is the commonly reported experience of astronauts viewing planet Earth from space and the subsequent reflection on and processing of this experience. The overview effect is associated with feelings of awe, self-transcendence, and a change of perspective and identity that manifest themselves in taking steps toward protecting the fragile ecosystem. In the current study, we investigated whether the overview effect can be obtained in school children when simulated using virtual reality (VR) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…According to Zelenski and Desrochers (2021), positive and self-transcendent emotions (e.g., awe, compassion, and gratitude) are particularly effective. Noticeably, they can be related to the overview effect (van Limpt-Broers, et al, 2020).…”
Section: Vr For Sustainability Awareness and Behaviour Changementioning
confidence: 99%
See 2 more Smart Citations
“…According to Zelenski and Desrochers (2021), positive and self-transcendent emotions (e.g., awe, compassion, and gratitude) are particularly effective. Noticeably, they can be related to the overview effect (van Limpt-Broers, et al, 2020).…”
Section: Vr For Sustainability Awareness and Behaviour Changementioning
confidence: 99%
“…The emotional effect of the earth view from space has been studied by Chirico et al (2018) in their work regarding awe (i.e., a feeling astonishment, wonder, and connectedness that humans experience of in front of wide spaces and elements). Awe is in fact a predictor of the overview effect (van Limpt-Broers, et al, 2020). The study by Quesnel et al (2019) shows how awe can increase the human connection with nature, potentially improving pro-environmental and pro-social behaviours, as well as wellbeing.…”
Section: The Overview Effect In Vrmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one study has manipulated awe and looked at subsequent learning outcomes associated with that awe experience. van Limpt-Broers et al (2020) have found evidence that feelings of awe elicited by immersive virtual reality are associated with greater learning outcomes in elementary school-aged children. In this study, participants were given lessons and conducted learning activities about space (e.g., astronauts, satellites, and the solar system) prior to the simulation.…”
Section: Awe As An Epistemic Emotionmentioning
confidence: 99%
“…Other research has focused on the emotional experience of the overview effect, with a particular focus on feelings of awe and self-transcendence [ 3 , 17 ]. For instance, it has been shown that a VR experience of the overview effect elicited an awe-inducing experience [ 14 ] and that for children high in dispositional awe the VR-induced overview effect was positively associated with their learning performance in the domain of nature conservation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%